2020
DOI: 10.7717/peerj.8644
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and related risk factors in oral mucosa diseases among residents in the Baoshan District of Shanghai, China

Abstract: Background Oral mucosal diseases (OMDs) encompass a variety of different types of diseases. Our aim was to evaluate the prevalence and related risk factors of OMDs among residents in the Baoshan District of Shanghai, China, and provide a scientific basis for prevention and control strategies. Methods A sample of 653 residents aged 17 to 92 years from the Baoshan community was investigated in 2014. Each resident was surveyed by questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…For the female police officer, the level of prevalence of RAS is relatively lower and oral leukoplakia is not found. Recent study in China showed the oral mucosal disorder is closely associated with psychological factors [ 9 ]. In contrary to Canadian police officers [ 30 ], where policewomen were reported to have greater mental disorder rates relative to the general population, policewomen in China mainly perform general affairs and might have lower psychological pressure so that they have less oral mucosal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the female police officer, the level of prevalence of RAS is relatively lower and oral leukoplakia is not found. Recent study in China showed the oral mucosal disorder is closely associated with psychological factors [ 9 ]. In contrary to Canadian police officers [ 30 ], where policewomen were reported to have greater mental disorder rates relative to the general population, policewomen in China mainly perform general affairs and might have lower psychological pressure so that they have less oral mucosal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent long term follow-up study found 5.6% OSF patients in Mainland China can transform into oral squamous cell carcinoma [ 22 ], indicating more attention should be focused on the screening and preventing of OSF. Past studies showed oral leukoplakia is related with the elderly age, smoking, and alcohol intake [ 9 , 23 ], however, the prevalence of OSF and oral leukoplakia in the doctor/nurse and police officer population in the Betel quid chewing city of Mainland China is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…El SBA es considerado multifactorial (11), habiéndose realizado en estos últimos años diferentes estudios de prevalencia y de factores de riesgo (11), tanto de factores locales (como son las prótesis dentales [10], sensibilidad de contacto, traumatismos, hábitos orales parafuncionales o disfunción de las glándulas salivares [12], infecciones locales, la más común cándidas [13,14]), como sistémicos, destacando menopausia, diabetes mellitus (13), hipertensión arterial, déficits nutricionales (8) o toma de fármacos (15).…”
Section: Etiología Y Factores Asociadosunclassified